'A Dose of Physick': Medical Practice and Confessional Identity within the Household. (4th January 2016) - Mann, Sophie
Abstract : In early modern England the place where most people experienced and treated illness was the home. Medical practices were therefore invariably centred on the family, and in many cases, sufferers diagnosed and nursed their ailments without seeking advice from a practitioner, instead favouring the counsel of a family member or friend. Centred on the personal transactions between patients, kin, neighbours, and in some cases a practitioner, how might the religiously plural context of the Reformation era have shaped these close social relationships? The subjects of this study belonged to two Catholic families: Nicholas Blundell (1669–1737) of Little Crosby in Lancashire, and Catharine Burton (1668–1714) of Bury St Edmunds in Suffolk. Focusing on the sickness experiences, lay healing practices and medical treatment described at length in their diaries, this essay asks three central questions. First, in what ways did confessionally opposed families integrate or separate from one another in relation to matters of health? Second, did these subjects forge more exclusive ties with medical practitioners of their own confession, or, conversely, did they find a way to coexist comfortably with, and interact in, the 'medical marketplace'? Third, by examining the practices through which religion and medicine interrelated within the household, I aim to challenge longstanding assumptions concerning the progressive 'secularization' or 'medicalization' of the sickbed. I hope to shed fresh light on the ways in which medical practices were embedded in social relations and community experiences; and to begin to unravel some of the complex channels through which confessional identity was experienced and expressed in relation to healing.